Evaluating privacy compliance and ethical standards for personal assistant AI under GDPR and CCPA - García Ramírez, Mariel (2025)
Privacy, legal compliance, and ethical concerns are some of the issues raised by the growing use of Personal Assistant Artificial Intelligence (PAAI) systems in daily life. Examples of these systems are Apple Siri and Amazon Alexa, technologies that are built into devices like smartphones, smart speakers, and smart devices at home that continuously process vast amounts of user data through behavioral profiling and voice recognition. These kinds of systems are getting attention because of the concerns regarding algorithmic responsibility, data governance, and consumer autonomy within digital ecosystems because of their dual role as data collectors and service facilitators. This thesis seeks to determine whether these assistants comply with two of the most significant privacy laws in the world: the General Data Protection Regulation (GDPR) and the California Consumer Privacy Act (CCPA). According to this study, privacy is reinterpreted as the preservation of relevant information in a variety of social contexts. This interpretation is based on the contextual integrity theoretical framework developed by Nissenbaum (2004). Applying frameworks such as Solove's (2006) taxonomy of privacy harms and Zuboff's (2020) critique of surveillance capitalism, the thesis develops a comprehensive method for evaluating how well Siri and Alexa comply with legal and ethical privacy standards. This point of view also includes the fact that frameworks support the thesis. Since Siri and Alexa have quite different data design principles, economic strategies, and regulatory scrutiny, the theoretical synthesis and literature review support the selection of these two systems as case studies. We provide a thorough comparative analysis of consent processes, third-party access, interface design, and data minimization strategies using these theoretical tools.